(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Swami Vivekananda is generally known as a prophet, a saint, a patriot, an immense lover of humanity, a great spiritual and religious leader and a heart wining orator. Very few know about his literary expressions, chiefly the poems composed by him. We cannot call him literary figure in general sense. Most of the Indian saints while giving their message to the world have produced the poetry of the highest order. None among these were the poets or the literary figures. These were the heavenly spirits and saints showing right path giving heavenly message to the society. Still whatever they have produced in the form of their message or writing has become the great literary treasure. Same is the case with Swami Vivekananda whatever he spontaneously expressed in the form of his poems has become the very expression of his soul, personality and his life giving message. Most of the poems of Vivekananda indicate his high ecstatic state, personal experiences, concerns, prophetic outlook, patriotic and spiritual view point in which they are shaped.